WHY THE BIPOLAR SYSTEM LIMITING THE EFFICACY OF THE U.S. SECURITY COALITION’S ECONOMIC SACTION ON RUSSIA: A NEOSTRUCTURAL REALISM PERSPECTIVE - Fajri, Harri (Jurusan Ilmu Hubungan Internasional, 2025)
This article examines the efficacy of economic sanctions within the context of the 2022 Russian invasion of Ukraine. Traditionally viewed skeptically by scholars, economic sanctions were reconsidered in the 1980s as potentially effective. This study evaluates U.S.-led sanctions aimed at deterring the invasion and weakening Russia's economic and military capabilities. Despite these efforts, Russia's economy rebounded in 2023, and its military actions continued. The research explores why the bipolar system limits the impact of the U.S. security coalition’s economic sanctions on Russia’s economy and has not effectively reduced Russia’s power to wage war on Ukraine. By applying neostructural realism theory, the article argues that as a revisionist great power pursuing a unipole position, China ensures that the U.S.’ proxy war with Russia is long and costly by offsetting U.S. economic sanctions. China achieves this through increased imports of Russian oil and gas, using its financial payment system, and exporting machinery and semiconductors to Russia. This support sustains Russia's economy and military capacity, highlighting the limitations of economic statecraft in a bipolar world where major powers counterbalance each other's influence. The study underscores the need to reassess economic sanctions in contemporary geopolitical conflicts.